Sensation-seeking in women does not affect their preference for Dark Triad male faces. (1st August 2018) - Brewer, Gayle; Carter, Gregory Louis; Lyons, Minna; Green, Jessica
Abstract: Women ( N  = 356) aged 16–68 years were recruited via online social networking sites and research participation websites. Participants were presented with 15 facial composite pairs (each pair including a high and low Dark Triad trait facial morph), and were asked to identify the most attractive individual either in the context of a short-term ( n  = 171) or long-term relationship ( n  = 185). Women also completed the Sensation-Seeking Scale (SSS-V, Zuckerman, 1994 ), containing boredom susceptibility, disinhibition, experience-seeking, thrill- and adventure-seeking subscales. Results indicate that women are averse to faces with high levels of narcissism, Machiavellianism, and psychopathy for both short- and long-term romantic relationships. Sensation-seeking does not predict preference for Dark Triad traits as a short-term or long-term partner. Findings replicate previous research indicating that women dislike male faces high on Dark Triad traits for both short- and long-term relationships and are consistent with research suggesting that the aversion to men high on Dark Triad traits is resistant to individual variation. Highlights: Women showed aversion to high Dark Triad faces. Aversion occurred for both short- and long-term relationships. Sensation-seeking did not predict preference for Dark Triad faces.